Polarization of Time and Income A Multidimensional Approach with Well-Being Gap and Minimum 2DGAP: German Evidence - Joachim Merz; Bettina Scherg (Institute for the Study of Labor (IZA), 2013)
A growing polarization of society accompanied with an erosion of the middle class experiences more and more attention at least in the German recent economic and social policy discussion. Our study contributes to the polarization discussion with respect to multidimensional theoretical measurement and empirical application in two ways: First, we propose extended multidimensional polarization indices based on a CES-type well-being function and present a new measure to multidimensional polarization, the mean minimum polarization gap 2DGAP. This polarization intensity measure provides transparency with regard to each singular attributes - important for targeted policies - and ensures at the same time its interdependent relations. Second, the empirical application - in addition to the traditional income measure - incorporates time as a fundamental resource for any activity. In particular, genuine personal leisure time will take care of social participation in the spirit of social inclusion/exclusion and Amartya Sen's capability approach. Instead of arbitrarily choosing the attributes' parameters in the CES well-being function, the interdependent relations of time and income will be evaluated by German Society. With the German Socio-Economic Panel (SOEP) and detailed time use diary data of the available German Time Use Survey (GTUS) 1991/92 and 2001/02 we quantify available and extended multidimensional polarization measures as well as our new approach for the polarization development of the working poor and the working rich in Germany. Results: Genuine personal leisure time in addition to income is an important polarization attribute. Compensation is of economic and static significance. In particular supported by the new minimum 2DGAP approach, multidimensional polarization increased over that decade in Germany.
Keywords: I32; D31; J22; 330; multidimensional polarization; intensity of time and income poverty and affluence; interdependent multidimensional time and income poverty and affluence; minimum multidimensional polarization gap (2DGAP); extended economic wellbeing; satisfaction/happiness; working poor; CES well-being function; German Socio-Economic Panel; German Time Use Surveys 1991/92 and 2001/02